2018
DOI: 10.1007/s00270-018-2010-4
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Bleomycin–Lipiodol Embolization (B/LE) for Symptomatic Giant Hepatic Hemangioma

Abstract: Transarterial B/LE is a safe and efficient alternative for controlling symptoms related to large hemangiomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 37 publications
0
29
0
9
Order By: Relevance
“…Substances used for TAE are, for example, metallic coils, polyvinyl alcohol, Gelfoam particles, and liquid agents such as N-butyl-2-cyanoacrylate and bleomycin-lipiodol [36][37][38]. A recent study including 23 patients and 29 HHs treated with TAE using bleomycin-lipiodol showed a 50% reduction in the hemangioma volume in 17 of 23 patients [39].…”
Section: Nonsurgical Managementmentioning
confidence: 99%
“…Substances used for TAE are, for example, metallic coils, polyvinyl alcohol, Gelfoam particles, and liquid agents such as N-butyl-2-cyanoacrylate and bleomycin-lipiodol [36][37][38]. A recent study including 23 patients and 29 HHs treated with TAE using bleomycin-lipiodol showed a 50% reduction in the hemangioma volume in 17 of 23 patients [39].…”
Section: Nonsurgical Managementmentioning
confidence: 99%
“…Multiple reasons for treatment, present in 39/231 patients (16.9%), always included symptoms. Three studies stated that the indication for treatment was either symptoms, fear of future bleeding, patients’ desire for treatment or tumour size, but did not specify how many patients underwent treatment for each indication [ 51 , 52 , 54 ]. Details are tabulated in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Biopsy was occasionally used in case of unsure diagnosis or if the study was conducted before widespread availability of CT and MRI [ 16 , 31 , 38 , 48 , 51 ]. Lipiodolization was performed with either pingyangmycin or bleomycin [ 8 , 31 , 38 , 45 , 47 , 50 , 52 54 ]. TAE/TACE procedures usually included the use of gelfoam [ 41 , 43 , 44 , 46 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has a sclerosing effect on endothelial cells with a nonspecific inflammatory reaction. 9 Bleomycin has been used in the treatment of symptomatic hepatic haemangioma 10 and focal nodular hyperplasia 11 as a vascular endothelial sclerosing agent during TAE. This has been demonstrated to be safe and efficient with good long-term symptomatic control and reduction in lesion size.…”
Section: Introductionmentioning
confidence: 99%